Kappa B site-dependent activation of the interleukin-2 receptor alpha-chain gene promoter by human c-Rel. - Tan, T H (1992)
The cis-acting control elements of the interleukin-2 receptor alpha-chain (IL-2R alpha) gene contain a potent kappa B-like enhancer whose activity can be induced by various mitogenic stimuli. Recent cloning of the p50 and p65 subunits of the kappa B-binding protein NF-kappa B complex revealed a striking sequence homology of these proteins with the c-rel proto-oncogene product (c-Rel). On the basis of this homology, we examined the potential role of c-Rel in controlling IL-2R alpha transcription. We now demonstrate that the recombinant human c-Rel protein binds to the kappa B element in the IL-2R alpha promoter and results in alteration of the DNA structure in the adjacent downstream regulatory elements containing the CArG box and the GC box. We found that human c-Rel can activate transcription from the IL-2R alpha promoter, but not the kappa B-containing human immunodeficiency virus type 1 promoter, upon cotransfection into Jurkat T cells. Furthermore, truncation of the carboxyl terminus of c-Rel results in a c-Rel mutant (RelNA) that (i) localizes exclusively in the nucleus and (ii) acts in synergy with wild-type c-Rel in activating transcription from the kappa B site of the IL-2R alpha promoter. Finally, induction of surface IL-2R alpha expression coincides with the induced levels of endogenous c-Rel and induced c-Rel binding to the IL-2R alpha kappa B site. Our study identified c-Rel as one component of the Rel/NF-kappa B-family proteins involved in the kappa B-dependent activation of IL-2R alpha gene expression. Furthermore, our results suggest that a Re1NA-like cellular factor (e.g., NF-kappa B p50 or p49 subunit) acts in synergy with c-Re1 during T-cell activation.